Evidence for enhanced convection of North Pacific Intermediate Water to the low‐latitude Pacific under glacial conditions. (20th January 2017) - Max, L.; Rippert, N.; Lembke‐Jene, L.; Mackensen, A.; Nürnberg, D.; Tiedemann, R.
Abstract: We provide high‐resolution foraminiferal stable carbon isotope (δ 13 C) records from the subarctic Pacific and Eastern Equatorial Pacific (EEP) to investigate circulation dynamics between the extratropical and tropical North Pacific during the past 60 kyr. We measured the δ 13 C composition of the epibenthic foraminiferal species Cibicides lobatulus from a shallow sediment core recovered from the western Bering Sea (SO201‐2‐101KL; 58°52.52′N, 170°41.45′E; 630 m water depth) to reconstruct past ventilation changes close to the source region of Glacial North Pacific Intermediate Water (GNPIW). Information regarding glacial changes in the δ 13 C of subthermocline water masses in the EEP is derived from the deep‐dwelling planktonic foraminifera Globorotaloides hexagonus at ODP Site 1240 (00°01.31′N, 82°27.76′W; 2921 m water depth). Apparent similarities in the long‐term evolution of δ 13 C between GNPIW, intermediate waters in the eastern tropical North Pacific and subthermocline water masses in the EEP suggest the expansion of relatively 13 C‐depleted, nutrient‐enriched, and northern sourced intermediate waters to the equatorial Pacific under glacial conditions. Further, it appears that additional influence of GNPIW to the tropical Pacific is consistent with changes in nutrient distribution and biological productivity in surface waters of the glacial EEP. Our findings highlight potential links between North Pacific mid‐depth circulation changes, nutrient cycling, and biological productivity in the equatorial Pacific under glacial boundary conditions. Key Points: Expansion of Glacial North Pacific Intermediate Water (GNPIW) to the tropical Pacific Glacial switch to additional influence of GNPIW at the Eastern Equatorial Pacific Enhanced GNPIW convection coincides with low‐latitude nutrient and marine productivity changes